Chlorambucil Cytotoxicity Reduction in Rats Through Bone Marrow, An In vivo Study - Nafie, Ebtesam H.O.; Khater, Eman; Awwad, Mohamed; Zowail, Mohamed; Hegazy, Kholud (Anti-Cancer Agents in Medicinal Chemistry, 2018)
Background: Bone Marrow (BM) has the self-renovation capacity and has been used recently in tumor medicine. Chlorambucil [CHB] is ordinarily utilized chemotherapy to treat varieties of malignancy patients. This investigation intended to gauge the effectiveness of BM as an in-vivo antimutagenic against CHB. Methods: The experimental design relies upon four classes; each class contains ten adult male albino rats as follows: control, rats infused orally with CHB for fourteen days, rats intravenously infused with BM through a tail vein one time, rats infused the mix of CHB and BM.The Anticancer capability of BM was assessed by cytogenetic assay and mitotic index. The declarations of the apoptosis- related genes were examined by RT-qPCR examination. Results: The present experiment demonstrated a curative effect of BM against the cytotoxic impact of CHB. Infusion of BM after chemotherapy helps to diminish the chromosomal aberration; increment mitotic index and decline the Bax/Bcl2 proportion compared with [CHB] class gather that prompts expanding the survival rate of influenced cells with chemotherapy cytotoxicity. Conclusion: The present study shows that bone marrow transplantation together after CHB infusion helps to increase genomic stability by diminishing structural chromosome abnormalities, diminishing the Bax/Bcl2 proportion and increasing the mitotic index.
Keywords: chromosomal aberration